The epidemiological follow-up process for suspected and confirmed cases of COVID-19 in migrant shelters on the northern border of Mexico from July to December 2020: Between contagion underestimation and containment - Rangel Gómez, María Gudelia; Cruz-Piñeiro, Rodolfo; Cappelletti, Valentina; López Jaramillo, Ana María (Frontiers in Public Health, 2023)
The elements that increase the risk factors for contagion from COVID-19 in shelters are associated with the turnover and overcrowding of the people in these areas, spending time together in common areas, the need for daily supplies, water availability and sanitation. Likewise, as noted in the “Report on the Effects of the COVID-19 Pandemic on Migrants and Refugees,” the shortage of food supplies, water, sanitizing material, adequate spaces for guaranteeing a safe distance, financial resources to guarantee the payment of rent and basic services, and the lack of medical or psychological care required by migrants, are problems that complicate the care of migrants and applicants for international protection housed there. Describe the functioning of shelters in the border cities under study in regard to the detection of suspected and confirmed cases of COVID-19 with mild symptoms among the migrant population housed there. The research was based on a qualitative methodological design with an ethnographic approach. The cities under study were Tijuana (Baja California), Nogales (Sonora), Ciudad Juárez (Chihuahua), Piedras Negras (Coahuila) and Heroica Matamoros (Tamaulipas). Study subjects: Shelters, refuges, nursing homes, foster homes and, in general, institutions, with or without a nonprofit charter, that provided humanitarian support specifically in the form of accommodation. The research instrument was the semi-structured, in-depth interview. Contrary to what was being speculated during the early weeks of the pandemic, migrant shelters on the northern border did not become sources of COVID-19 infection, since in a universe of 78 shelters analyzed, only seven had confirmed cases and the classification of “outbreaks” was only used in two shelters. In this respect, the control/containment of contagion has been successful. A preventive, containment logic was detected, which included the isolation of all suspected but unconfirmed cases, without transparency or clear agreements on the human and financial resources required to maintain isolation areas. However, the way these study contexts implemented epidemiological surveillance, control and prevention protocols contained elements that interfered with monitoring in these spaces and led to the underestimation of the phenomenon.